Beryllium-10 concentrations in the hyper-arid soils in the Atacama Desert, Chile: Implications for arid soil formation rates and El Niño driven changes in Pliocene precipitation. (1st July 2015) - Wang, Fan; Michalski, Greg; Seo, Ji-Hye; Granger, Darryl E.; Lifton, Nathaniel; Caffee, Marc
Abstract: Meteoric 10 Be concentrations in soil were measured to understand the mechanism, timescale, and climatic dependence of soil formation in the hyper-arid Atacama Desert. The observed systematic decline of soil 10 Be concentrations with depth has been reproduced using a simple model that assumes soil matrix, including 10 Be, builds up as layers over time while 10 Be decays in situ . This suggests a mechanism of soil accumulation via atmospheric deposition, which is in agreement with stable isotopic evidence. The model estimates an age of ∼6.6 ± 0.4 Ma for the total soil profile. Small discrepancies between the model and observations are likely mainly due to changes in precipitation rates that can impact 10 Be delivery rates and 10 Be movement within the profile. Interpreted in this way, the 10 Be data suggest drying in the Atacama after ∼4.7 Ma, and returning to an insignificant wet period at ∼1 Ma, which was possibly connected to El Niño- or La Niña-like climate change.